Synthesis and Structure of a 2D-Supramolecular Compound: [Cu(Phen)2Cl]+Cl+3.5H2O - Bi, Jian-Hong; Meng, Xiang-Chun; Huang, Zi-Xiang; Hu, Nai-Liang (Asian Journal of Chemistry, 2010)
A new 2D-supramolecular compound of formula [Cu(Phen)2Cl]·Cl·3.5H2O (phen = 1,10-phenanthroline) has been synthesized and determined by X-ray diffraction. The crystal is monoclinic, space group C2/c with unit cell parameters: a = 23.354(2)Å, b = 30.289(3)Å, c = 7.4973(6)Å. α = 90º, β = 97.744(4)º, γ = 90º, v = 5255.1(8)Å3, z = 8, Dc = 1.441 Mg/m3, Mr = 569.90, F(000) = 2336 and μ = 1.072 mm-1. The final R and wR are 0.0734 and 0.2139, respectively for 5997 observed reflections with I>2σ(I). The center copper(II) ion is five-coordinated in a square pyramidal geometry. The compound is in 2D-supramolecular state.